Bora-amidinate complexes of lanthanide(II) metals - Harder, Sjoerd; Naglav, Dominik (European Journal of Inorganic Chemistry, 2010)
Reaction of (2-MeN-α-MeSi-benzyl) Ln·(thf) (Ln = Yb, Eu and Sm) with one equivalent of DIPP(H)N-BH-N(H)DIPP (NBN-H, DIPP = 2,6-iPr-phenyl) gave the first Ln boraamidinate complexes which crystallized in the presence of THF as NBN·Ln·(thf) . Although only the Sm and Eu complex crystallize isomorphic, all three show similar structures. The very small N-Ln-N' bite angles of 59.74(6)63.28(9)° leave a large part of the metal coordination sphere available for neutral thf ligands. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.